Programa De Atención E Intervención Psicosocial Con Metapropòsito De Construcción De Habilidades Psicosociales Para La Vida Desde La Gestión Del Riesgo, Frente A La Pérdida Del Sentido De Vida En Estudiantes Vinculados A Las Ied Del Municipio De Cajicá - Páez Moreno, Jaime Alberto (Universidad Antonio Nariño, 2023)
Human beings are constantly exposed to existential crises due to adaptability factors, and in some cases, they experience existential emptiness (Aquino T. A., 2016). ¨The existential vacuum is caused by the loss of instinct and tradition, which causes man not to know what he should do (Aquino T. A., 2017)